2017
DOI: 10.3390/biology6020030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Real-World HCV Genotype 2-Infected Japanese Patients with Sofosbuvir plus Ribavirin

Abstract: The aim of this study was to characterize the treatment response and tolerability of sofosbuvir plus ribavirin therapies in Japanese patients infected with hepatitis C virus (HCV) genotype (GT)-2. This retrospective study analyzed 114 Japanese HCV GT-2 patients treated for 12 weeks with 400 mg of sofosbuvir plus weight-based ribavirin daily. This treatment led to higher sustained virologic response at 12-weeks post-treatment (SVR12) rates in both treatment-naïve and treatment-experienced patients. The efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
(59 reference statements)
2
13
3
Order By: Relevance
“…Although previous studies have reported lower SVR rates in patients with liver cirrhosis, different subtypes of genotype 2, a high baseline viral load, and prior treatment failure, we found no factors that were significantly related to the SVR rate in our study, probably because of the small sample size of those who failed to achieve SVR. A prior history of HCV treatment is regarded as a risk factor for treatment failure.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Although previous studies have reported lower SVR rates in patients with liver cirrhosis, different subtypes of genotype 2, a high baseline viral load, and prior treatment failure, we found no factors that were significantly related to the SVR rate in our study, probably because of the small sample size of those who failed to achieve SVR. A prior history of HCV treatment is regarded as a risk factor for treatment failure.…”
Section: Discussioncontrasting
confidence: 98%
“…A prior history of HCV treatment is regarded as a risk factor for treatment failure. The proportion of patients with a history of prior HCV treatments was lower in the current study (13.4%) than in previous real-world studies (28%-34.2%), 14,16,17 which may explain the high SVR rate in this study. Some studies have reported low SVR rates in patients with cirrhosis who received 12 weeks of treatment.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The role of RBV adherence might affect SVR. Japanese real‐world data on the efficacy of SOF + RBV for genotype 2 infections have been reported, and there is disagreement on the impact of RBV dose reduction on SVR …”
Section: Introductionmentioning
confidence: 99%